Beyond Stability: Democratic Risks and Governance Challenges of Extending Village Head Tenure in Indonesia - Ainia Fany Nur Khofifah; Falih Suaedi (Journal of Social and Policy Issues, 2025)
This study examines the democratic risks and governance challenges arising from the extension of village head tenure in Indonesia. While longer tenure is often justified as a means to ensure policy continuity and effective realization of development visions, excessive concentration of power may foster authoritarian tendencies and weaken democratic accountability at the village level. Using a qualitative library research approach, this study analyzes primary legal sources, particularly Law Number 3 of 2004 concerning amendments to Law Number 6 of 2014 on Villages, complemented by secondary sources such as books, academic journals, theses, and dissertations. Data were analyzed through descriptive qualitative methods to explore the implications of extended tenure on local governance. The findings indicate that extending the village head’s term presents complex consequences, including increased risks of corruption, imbalanced control over economic and political resources, and reduced leadership rotation. Moreover, prolonged tenure may hinder policy innovation and encourage the emergence of political dynasties or oligarchic structures, thereby threatening democratic principles of inclusivity, fairness, and representation. The study concludes that without strong safeguards, tenure extension may undermine participatory governance and sustainable village development. Therefore, the research recommends limiting maximum tenure duration, strengthening transparency and accountability mechanisms, and reinforcing legal frameworks to ensure that village governance remains democratic, inclusive, and responsive to community needs.